Pengelolaan Ekowisata Berbasis Konservasi Alam pada Kawasan Kandi sebagai Lokasi Pembangunan Taman Kehati Emil Salim Sawahlunto - Hendrita, Juli; Helmi, Helmi; Novarino, Wilson (Jurnal Sosiologi Andalas, 2024)
Participatory management of conservation areas requires collaboration in management. Multistakeholder collaboration and community participation in conservation area management are essential in realising the awareness of each element involved. Kandi area is situated in Sawahlunto City. a former location of coal mining. After the close of the mining this area is used for a tourism destination with various attractions such as Kandi Fruit Park, Kandi Animal Park, Camping ground, Horse Racing Field, and Circuit. Taman Kehati Emil Salim Sawahlunto will also be built in this location with an area of 24 ha containing local biodiversity. The purpose of this study is to analyse engagement of multi-stakeholders, tourist perceptions and community participation in the Kandi area. The approach used in this research is mixed method with descriptive analysis. The respondents of this research were the Head of Destination Division of Sawahlunto City, Head of Tourism Objects Division of Kandi Area, and Head of UPTD Plant Nursery of Kandi Fruit Garden, tourists, and community. Data were collected by means of literature study, observation, pre-research, research, interviews and questionnaires. The results of the study are there is no engagement between stakeholders, because the tourist attraction is managed by the government of Sawahlunto City. however, Taman Kehati Emil Salim Sawahlunto involves multi-stakeholders. Then, tourists who visit are satisfied with the vast land, but tourists are unsatisfied with the sanitary of tourist attractions and incomplete tourist facilities. Community participation in the organization of biodiversity park management indicates that the surrounding community cares about nature conservation.